Posterior reversible encephalopathy syndrome caused by presumed Takayasu arteritis - Ki Wuk Lee; Sang Taek Lee; Heeyeon Cho (Korean Pediatric Society, 2016)
Takayasu arteritis (TA) is a chronic inflammatory disease of unknown etiology that affects mainly the aorta, main aortic branches, and pulmonary arteries. Diverse neurological manifestations of TA have rarely been reported in children. Posterior reversible encephalopathy syndrome (PRES) is a neuroradiological condition that presents with headache, seizure, visual disturbances, and characteristic lesions on imaging. Inflammatory condition and severe hypertension in TA can cause PRES. We report of a 5-year-old girl with presumed TA who presented with PRES and chronic total occlusion in the renal artery. The findings on magnetic resonance imaging suggested PRES. Left nephrectomy was performed for total occlusion of the left renal artery, and the confirmatory diagnosis of TA was based on the pathologic findings of the renal artery.